Impact of Caring Climate, Job Satisfaction, and Affective Commitment on Employees’ Performance in the Banking Sector of Bosnia and Herzegovina - M. Sait DINC; Vesna PLAKALOVIC (Eurasian Journal of Business and Economics, 2016)
The main purpose of this paper is to examine the impact of caring climate, employees' job satisfaction, and affective commitment on employees' job performance in a banking sector. This study proposes that caring climate has a significant direct effect on overall job satisfaction, affective commitment, and job performance. Moreover, it suggests that caring climate has an influence on job performance through overall job satisfaction and affective commitment. Additionally, affective commitment is considered to be a mediator in the relationship between overall job satisfaction and job performance. In this study, the relationships among the variables were evaluated using factor analysis, descriptive statistics, correlations, and regression. The results based on a sample of 152 employees from one public and three private banks in the Federation of Bosnia and Herzegovina support the hypotheses. This study demonstrates that caring climate has a significant direct influence on overall job satisfaction, affective commitment, and job performance. Furthermore, caring climate has an indirect effect on job performance. Finally, this research discovers an indirect relationship between overall job satisfaction and employees’ job performance through a mediating role of affective commitment.